Getting a seat at the table: Strengthening women' tenure rights and participation in community forestry in Uganda - Mwangi, Esther (Center for International Forestry Research, 2017)
Presented by Esther Mwangi (CIFOR), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.)